2010
DOI: 10.1007/s12149-010-0369-7
|View full text |Cite
|
Sign up to set email alerts
|

Lung ventilation–perfusion imbalance in pulmonary emphysema: assessment with automated V/Q quotient SPECT

Abstract: V/Q quotient SPECT appears to be more sensitive to detect emphysematous lungs compared with morphologic CT in patients with emphysema. SD and kurtosis of V/Q profile can be adequate parameters to assess the severity of lung V-Q imbalance causing gas-exchange impairment in patients with emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…Previously in clinical studies, Jogi et al have demonstrated that V/Q SPECT is sensitive to COPD-related pathologies (13), and Suga et al have quantified the V/Q mismatch due to emphysema in a per-voxel manner (14). Our results affirm that V/Q methodologies, being functional measurements, are sensitive to early pathologic changes that lead to COPD but may not be apparent, even at a higher resolution, with anatomic imaging systems such as CT. Because V/Q imaging is a common nuclear medicine technique and SPECT/CT systems are increasingly used (21), V/Q measurement could play an important role in the diagnosis, treatment, and further understanding of COPD (13,22,23).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previously in clinical studies, Jogi et al have demonstrated that V/Q SPECT is sensitive to COPD-related pathologies (13), and Suga et al have quantified the V/Q mismatch due to emphysema in a per-voxel manner (14). Our results affirm that V/Q methodologies, being functional measurements, are sensitive to early pathologic changes that lead to COPD but may not be apparent, even at a higher resolution, with anatomic imaging systems such as CT. Because V/Q imaging is a common nuclear medicine technique and SPECT/CT systems are increasingly used (21), V/Q measurement could play an important role in the diagnosis, treatment, and further understanding of COPD (13,22,23).…”
Section: Discussionsupporting
confidence: 76%
“…V/Q SPECT imaging, on the other hand, is a well-established nuclear medicine technique that provides spatial information regarding the 2 core processes of respiratory gas exchange, ventilation of alveolar units and perfusion of the pulmonary capillary beds (11), and the results of this technique correlate well with those derived from MIGET (12). SPECT V/Q is commonly used in the diagnosis of pulmonary embolism but has been shown to be sensitive to early indicators of COPD in addition to being capable of identifying comorbid disease and distinguishing pathophysiologic changes (13,14). Furthermore, coregistration of nuclear imaging data to CT images allows for greater insight into the anatomic position of lung dysfunction and structural information such as the distribution of emphysema.…”
mentioning
confidence: 99%
“…HRCT imaging detects early emphysema by identifying pulmonary tissue with radiologic attenuation below a predetermined threshold, findings that roughly correlate with a low DL CO and pathologic evidence of emphysema (74)(75)(76)(77)(78)(79)(80). Although several studies have shown that a significant proportion of asymptomatic smokers have HRCT evidence of emphysema (78,(81)(82)(83), early HRCT findings of ''emphysema'' are not proven to be correlated directly with lung destruction (84)(85)(86)(87)(88)(89)(90). Hyperpolarized gas diffusion-weighted magnetic resonance imaging has also been used to identify emphysema, with a correlation of elevated levels of the apparent diffusion coefficient with decreased DL CO (91).…”
Section: Early Detection Of Lung Destructionmentioning
confidence: 99%
“…Jogi et al [10] have shown the ability of this technique to identify early disease and stage disease severity in COPD patients. Further, Suga et al [11] have quantified the impact of emphysema on V/Q in the lungs of COPD patients.…”
Section: Introductionmentioning
confidence: 99%